Acoustic Studies of the Effect of X-ray Irradiation on the Dynamic Drag of Dislocations in LiF Crystals - Petchenko, G.O. (Ukrainian Journal of Physics, 2022)
The dislocation resonance in LiF single crystals with the residual deformation ε = 1.5% is studied by the pulsed method in the range of radiation doses 0–660 R and the frequency range 22.5–232.5 MHz at room temperature. Based on the analysis of the obtained results, it is established that the X-ray irradiation of the crystals results in a significant change of the frequency and amplitude localizations of the dislocation resonance due to the variation of the mean effective length of a dislocation segment, whereas the viscosity coefficient B remains constant.